Pemberdayaan Kader Remaja Melalui Peningkatan Sarana Pemeriksaan Kesehatan Dasar di Posyandu Remaja - Husnah, Ridni; Andolina, Nuari; Adienda, Syfanea (LPPM STIKES Guna Bangsa Yogyakarta, 2024)
Adolescence is a time of storm and stress so it requires health services that care for teenagers. Youth Posyandu is one of the Community Resource Health Efforts (UKBM) that is managed and organized by, for, for and with the community, including adolescents in the implementation of health development. The Youth Posyandu in Bengkong Indah Village, Batam City has been formed, but there is still a lack of knowledge of peer cadres and infrastructure for basic examination of the Youth Posyandu, so that the Youth Posyandu runs less than optimally. The purpose of this activity is to give me a lesson for youth cadres on how to conduct an initial examination during the youth posyandu and complete the facilities of the youth posyandu that are not yet available. The activity was carried out at the Healty teenagers posyandu, Bengkong indah village, Batam city with a target of 7 peer cadres. The form of activities is the restructuring of peer cadres, health education and training for peer cadres. The activity was carried out well and smoothly, where the Youth Knowledge using the basic examination tool of the youth posyandu after being given training increased to 4 people or (57%), while the knowledge of adolescents decreased from 5 people (71%) after being given training to 1 person (14%). After this activity ends, it is hoped that the youth posyandu will be more optimal in the implementation of its examinations and activities will run regularly with the support of the health center.